Nontechnical guide to petroleum : geology, exploration, drilling and production - Hyne, Norman J. (Endeavor Business Media, LLC, 2019)
"A book on upstream operations. Readers will learn how oil and gas are formed, how to find commercial quantities, how to drill, evaluate, and complete a well"-- Provided by publisher.
Keywords: Petroleum -- Geology.; Petroleum engineering.; Petroleum -- Prospecting.; elektronické knihy; electronic books